Introduction of TPACK in Mathematics Education Realm - Yenny Anggreini Sarumaha (Intersections, 2020)
Mathematics education is one of the fields that agrees about the importance of integrating technologies into instructional activities in the classroom. However, only understanding technologies does not full fill the criteria of effective teachers, they have to be prepared and grasp the ideas of combining technologies, pedagogical, and content knowledge. This present study is a literature review which aimed at answering two mains questions namely, what is the TPACK framework and how does it influence our education system. Data were collected from articles related to technologies, ICT, and TPACK from thematic journals. The results found that TPACK is a well-known theoretical approach studying the pre-service teachers’ use of ICT. TPACK is accepted as an important framework for defining how well teachers integrate technologies in their classroom. TPACK model shows an effective way of thinking about integrating technologies along with pedagogies, and content knowledge. It has been developed for twenty-first century skills and used as a framework for developing teachers’ readiness toward the twenty-first century skills.